2009
DOI: 10.1111/j.1468-2419.2009.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for evaluating the effectiveness of middle managers' training courses: evidence from a major banking organization in Greece

Abstract: Contemporary management thinking embraces the organizational training theory that sustainable success rests, to a great extent, upon a systematic evaluation of training interventions. However, the evidence indicates that few organizations take adequate steps to assess and analyse the quality and outcomes of their training. The authors seek to develop the existing literature on training evaluation by proposing a new model, specific to management training, which might encourage more and better evaluation by prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 59 publications
3
33
0
8
Order By: Relevance
“…The empirical models obtained in this research are in agreement with the scientific literature on TD&E in demonstrating the importance of psychosocial support to learning in predicting the impact of training at work (Alfandi, 2016;Galanou, & Priporas, 2009). The variables of training impact, both in terms of amplitude, depth and competences presented acceptable results since the factors unit of work and immediate manager of the predictive variable of learning support demonstrated that it has a strong influence on the training results in the environment job.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The empirical models obtained in this research are in agreement with the scientific literature on TD&E in demonstrating the importance of psychosocial support to learning in predicting the impact of training at work (Alfandi, 2016;Galanou, & Priporas, 2009). The variables of training impact, both in terms of amplitude, depth and competences presented acceptable results since the factors unit of work and immediate manager of the predictive variable of learning support demonstrated that it has a strong influence on the training results in the environment job.…”
Section: Discussionsupporting
confidence: 86%
“…Galanou and Priporas (2009) also identified that training contributed to increased productivity and that the satisfaction level of the team was increased by the training evaluated by the authors. The impact of training on the job generates, in fact, effective contributions to the acquisition and mastery of professional skills of managers (D'Netto, Bakas, & Bordia, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Even though there are numerous researchers in training program evaluation, most of them measure perceptions and level of use for example, Phillips (2003), Al-Athari & Zairi (2002), Green (2004) and Al-Hatmi (2009). Generally according to Galanou and Priporas(2009) ), citing Kaplan and Norton (1996) claim also that "training programs generally lack practicability and their impact has not been systematically evaluated" makes several important points" (p. 235). They further states that to achieve the best quality results in investigation the impact of training programs that more research is needed in order to move away from the unplanned and poorly idea conceived(p. 235).…”
mentioning
confidence: 99%
“…H14: Não haverá diferença de opinião entre participantes e chefias nas avaliações de suporte psicossocial, suporte material e impacto do treinamento no trabalho (Abbad & Meneses, 2003;Santos Junior, 2012;Galanou e Priporas, 2009;Homklin et al, 2013;Homklin et al,2014;Pham et al, 2012;Yotamo, 2014).…”
Section: Objetivo E Hipóteses Do Estudounclassified